2018
DOI: 10.1111/aos.13733
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of retinal neurodegeneration with measures of peripheral autonomic neuropathy in type 1 diabetes

Abstract: PurposeTo evaluate the relationship of neuroretinal layer thickness with sensitive measures of cardiovascular autonomic neuropathy in diabetic patients with non‐proliferative diabetic retinopathy (NPDR).MethodsTwenty‐seven eyes of 27 patients with type 1 diabetes presenting with mild‐to‐moderate NPDR were compared to 27 healthy control (HC) eyes matched for age and gender. The total macular volume (TMV) and the volumes of individual neurosensory layers in the macula were analysed from spectral domain optical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 47 publications
(107 reference statements)
0
12
0
Order By: Relevance
“…The increased blood oxygenation levels in retinal veins have been attributed to several disease-specific changes in diabetic retinopathy leading to a reduced oxygen consumption in retinal tissue: Predominantly, diabetes-induced microvascular changes such as basement membrane thickening, reduced capillary density and shunt vessel formation may lead to reduced tissue perfusion and hence limit oxygen uptake and distribution in the retina (Pemp & Schmetterer 2008;Czak o et al 2018). In addition, neuroretinal tissue loss mainly of the inner retinal layers, which increases with diabetes duration (Pemp et al 2018), could also reduce retinal oxygen consumption. Increased total retinal blood flow in diabetic retinopathy and the higher affinity of oxygen to glycosylated haemoglobin, which is elevated in diabetes patients, may as well account for an oxygenation increase in retinal veins and also in retinal arteries (Bek 2013;Klefter et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The increased blood oxygenation levels in retinal veins have been attributed to several disease-specific changes in diabetic retinopathy leading to a reduced oxygen consumption in retinal tissue: Predominantly, diabetes-induced microvascular changes such as basement membrane thickening, reduced capillary density and shunt vessel formation may lead to reduced tissue perfusion and hence limit oxygen uptake and distribution in the retina (Pemp & Schmetterer 2008;Czak o et al 2018). In addition, neuroretinal tissue loss mainly of the inner retinal layers, which increases with diabetes duration (Pemp et al 2018), could also reduce retinal oxygen consumption. Increased total retinal blood flow in diabetic retinopathy and the higher affinity of oxygen to glycosylated haemoglobin, which is elevated in diabetes patients, may as well account for an oxygenation increase in retinal veins and also in retinal arteries (Bek 2013;Klefter et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms affecting peripheral nerves in diabetes are many, including microangiopathy, hypoxia and metabolic factors,12 rendering the diabetic nerve more sensitive to compression 13. Retinopathy is a frequent complication seen in diabetes, and there is an association between retinopathy and diabetic neuropathy,14 15 as well as between ocular neurodegenerative changes and diabetic neuropathy 16 17. Retinopathy might hence be used as a proxy variable for neuropathy.…”
Section: Introductionmentioning
confidence: 99%
“…Choi et al observed that retinal nerve fibre layer thickness and ganglion cell–inner plexiform layer thicknesses are independently associated with cardiac autonomic function, assessed by heart rate variability (with deep breathing and a change in posture from lying to standing position). Total macular and inner retinal layer volumes have also been reported to be associated with heart rate variability (a measure of autonomic neuropathy) in individuals with diabetes …”
Section: Diabetic Peripheral Neuropathymentioning
confidence: 99%